(3GdhXGFa GdGSJQGJjLjI aj EOGQI GdehGQO GdHTQjI (B/s - (3GdYRGhj, fLe YHO Gddgs; (3MSjf, LhGO YHGS s ((3YeGf(B: s (3GdjGRhQj ddfTQ hGdJhRjY(B, s, 2010)
(3JMdjd GdhXGFa h JUejegG h JNWjW GdehGQO GdHTQjI , GSJbWGH h GNJjGQ h JYjjf GdJhXja , GdCLhQ h GdQhGJH h GdJOQjH h Jbjje GdhXGFa , GdJMajR h GdQVG GdhXjaj h Jbjje GdCOGA , GdefGN h GdhdGA GdJfXjej h UjGfI GdehXa , GdYdGhI h GdJQbjI h Gdfbd h CNjQG GfJgGA NOeI GdehXa h GMGdJg Ydi GdJbGYOs
Keywords: (3EOGQI GdehGQO GdHTQjIs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs; (3dEOGQI GdCaQGOs